Health assessment in nursing. - Weber, Janet; Kelly, Jane H. (New York, United States : Wolter Kluwer / Lippincott Williams & Wilkins, 2010)
An introductory level health assessment text for RN-level students. It presumes no prior knowledge of health assessment
Includes index
Keywords: Nursing assessment; Nursing assessment -- Methods